Fine adjustment of interfacial potential between pH-responsive hydrogels and cell-sized particles - Monzel, Cornelia; Veschgini, Mariam; Tanaka, Motomu (Langmuir, 2015)
We quantitatively determined interfacial potentials between cell-sized particles and stimulus-responsive hydrogels using a microinterferometer. The hydrogel is based on physically interconnected ABA triblock copolymer micelles comprising an inner biocompatible PMPC block and two outer pH-responsive PDPA blocks. The out-of-plane temporal fluctuation in the position of the cell-sized particles was calculated from changes in the interference pattern measured by Reflection Interference Contrast Microscopy (RICM), thus yielding the particle-substrate interaction potential V (Δh).